Design and simulation of metamaterials and structure for high frequency application - Ong, Ming Sheng. (2011)
Electromagnetic Metamaterial (MTM) generally defines as artificial material effectively homogenous electromagnetic structure with unusual properties not readily available in nature. In this Report it deliver the infancy years for the MTM, which emerged from the first experimental demonstration of a Left-Handed (LH) structure in 2000, the vast majority of the group involved in research on MTM had been focusing on investigating from physic point on view due to the fundamental properties of LH were predicated by Veselago in 1967. Thus the trend was on the Split Ring Resonator (SRR) structure. On the other hand in 1940, readily available Transmission Line (TL) structure approach for the MTM by Brillion and Pierce, both of them had utilized the series-capacitance/ shut-inductance equivalent circuit model for analyzing on Left Hand (LH) MTM. In fact theoretical “backward-wave” uniform TL, without any suggestion for a practical implementation. Accordingly on research of SRR is not practical because of three main reasons not application to planar micro circuits, narrow-band due to requirement of operation near SRR resonance, lossy due to requirement of operation near SRR resonance. Hence, two type of structure was simulated for comparison and found out TL structure has a better high resonant frequency and lesser insertion loss. Therefore I had adopted an engineering approach, based on a generalized transmission line (TL) concept and developed a novel design of TL MTM and it geometry was also designed for further fabrication, with the latest technology, is achievable. Result has also proven that having series of supplementary unit-cell of the TL structure leads have a high potential for further studies.